2020
DOI: 10.37311/jsscr.v2i2.6980
|View full text |Cite
|
Sign up to set email alerts
|

Formulasi Sediaan Masker Gel Peel-Off dari Ekstrak Buah Tomat (Solanum Lycopersicum L.) Beserta Uji Aktivitas Antioksidan

Abstract: Tomatoes are well-known as the source of antioxidants due to the content of lycopene, i.e., a potential free radical inhibitor. Gel peel-off masks are among the chemical products containing antioxidants. The first step of the study was extracting tomato fruits by macerating the fruits using alcohol solvents 96%. The obtained thick extract was used as the material of the gel mask; the percentage of the extract comprised 3% (F1), 5% (F2), and 7% (F3), and it used PVA basis 11% and viscolam 3%. According to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
3
Order By: Relevance
“…The results of phytochemical screening showed that the aqueous extract of yellow potato tubers gave positive results on flavonoids. Flavonoids act as antioxidants by donating hydrogen atoms or through their ability to chelate metals, in the form of glucosides (containing glucose side chains) or in free forms called aglycones [17]. The positive flavonoid content is the part that contains high antioxidants equivalent to vitamin C, so the presence of these metabolite compounds encourages anti-aging effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…The results of phytochemical screening showed that the aqueous extract of yellow potato tubers gave positive results on flavonoids. Flavonoids act as antioxidants by donating hydrogen atoms or through their ability to chelate metals, in the form of glucosides (containing glucose side chains) or in free forms called aglycones [17]. The positive flavonoid content is the part that contains high antioxidants equivalent to vitamin C, so the presence of these metabolite compounds encourages anti-aging effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…Test time This drying is expected to obtain a good film coating formulation for application, apart from that it is also related to comfort when used. Expected drying time for a peel-off gel mask produced is between 15-30 minutes (Zubaydah et al, 2020).…”
Section: Drying Time Testmentioning
confidence: 99%
“…Masker gel terkadang disebut sebagai masker peel-off yang merupakan bentuk masker yang cepat dan mudah digunakan karena dapat dilepas setelah dikeringkan (Muflihunna et al, 2019) Biasanya, masker peel-off berbentuk pasta atau gel yang bila dioleskan ke kulit wajah akan meninggalkan lapisan tipis dan tembus cahaya. Masker akan mengering dalam 15 hingga 30 menit, dan lapisan film dapat terkelupas dari permukaan kulit wajah (Zubayday & Fandinata, 2020). Salah satu dari sekian banyak manfaat masker gel peel-off dibandingkan jenis masker lainnya adalah bentuk sediaan gelnya yang dapat secara efektif dan sederhana menenangkan dan membersihkan wajah (Muflihunna et al, 2019) Masker peel-off juga memiliki kemampuan untuk meningkatkan elastisitas kulit wajah, mengurangi kusam, mengangkat sel kulit mati, dan melindungi keremajaan kulit.…”
Section: Pendahuluanunclassified
“…Available online at www.jurnalfarmasihigea.org e-ISSN : 2541-3554 p-ISSN : 2086-9827 dengan ketentuan daya sebar sediaan topikal adalah 5-7cm(Zubayday & Fandinata, 2020).Uji HedonikDerajat kesukaan sediaan farmasi terhadap aroma, bentuk, dan warna menggunakan persentase konversi frekuensi digunakan untuk mengkaji data dari hasil uji hedonik.Panelis ini telah memenuhi prasyarat untuk disajikan di panel dan sudah terbiasa dengan karakteristik sensori hidangan yang sedang dievaluasi. Kemampuan berikut diperlukan untuk panelis: (a) kemampuan mengidentifikasi, membedakan, membandingkan, dan membedakan keterampilan hedonis; (b) memperhatikan aspek organoleptik; (c) kesediaan untuk memiliki waktu; dan (d) kemampuan memperhatikan aspek organoleptik.…”
unclassified